For a reframing of women’s entrepreneurship from three philosophical views on gender and power - Fabrício, Joiceli dos Santos; Vizeu, Fabio (REGEPE Entrepreneurship and Small Business Journal, 2024)
Objective: This text is an essay that discusses the concept of female entrepreneurship from the re-signification posed by the idea of gender relations, where these are considered as asymmetrical power relations, encompassing violence as the result of this condition. Our argument is built especially from the perspective of three authors: in the thinking of the historian Joan Scott, the philosopher Michel Foucault and the philosopher Hannah Arendt. Thesis: Their theoretical proposals allow us to reconstruct views about women as a historical construction based on power and control relations, on the one hand, and the exercise of violence as the main mechanism of patriarchy’s domination over the feminine. Relevance/Originality: This is how we argue that Female Entrepreneurship manifests itself in a context of violence, as it expresses the different forms of violence against women as a socially constituted event, highlighting the fact that, in the culture of capitalism, undertaking is an activity of power and, precisely for this reason, is usually denied to the female presence. Social/Management contributions: In addition, violence is a reaction to entrepreneurial women and works as an illegitimate resource used by the aggressor to maintain the patriarchal status quo, based on an asymmetrical view of women’s power and submission to men. Consequently, violence increases the more women are equal to men in spaces of power, suffering greater attacks from different forms of violence.